AI-2E Family Transporter Protein in Lactobacillus acidophilus Exhibits AI-2 Exporter Activity and Relate With Intestinal Juice Resistance of the Strain - Li, Xiefei; Fan, Xiankang; Shi, Zihang; Xu, Jue; Cao, Yingying; Zhang, Tao; Pan, Daodong (Frontiers in Microbiology, 2022)
The function of the autoinducer-2 exporters (AI-2E) family transporter protein of Lactobacillus acidophilus is still unclear. The phylogenetic analysis was used to analyze the relationship between the AI-2E protein of the L. acidophilus CICC 6074 strain and other AI-2E family members. Escherichia coli KNabc strain was used to verify whether the protein has Na+ (Li+)/H+ antiporter activity. The AI-2E protein overexpression strain was constructed by using the pMG36e expression vector, and the overexpression efficiency was determined by real-time quantitative PCR. The vitality and AI-2 activity of L. acidophilus CICC 6074 strains were determined. The results showed that the AI-2E protein of Lactobacillus formed a single branch on the phylogenetic tree and was closer to the AI-2E family members whose function was AI-2 exporter group I. The expression of AI-2E protein in the E. coli KNabc strain did not recover the resistance of the bacteria to the saline environment. Overexpression of AI-2E protein in L. acidophilus CICC 6074 could promote the AI-2 secretion of L. acidophilus CICC 6074 strain and enhance their survival ability in intestinal juice.